(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To evaluate the efficacy of Khanda Pippali Avaleha in the management of Amlapitta 2 and to compare the efficacy of Khanda Pippali Avaleha with a standard drug. Materials and Methods: A total of 30 clinically diagnosed patients were selected from OPD/IPD of Panchakarma, Department of Rishikul Campus, Haridwar, and randomly categorized into two equal group. In Group A, Khanda Pippali Avaleha was administered orally in a dose of 10 g. Period of the study was for 60 days along with follow-up after 1 month. In control group, omeprazole was given in the dose 20 mg once a day for 60 days empty stomach. The assessment was done on the basis of classical symptomology of Amlapitta. Results and Discussion: Obtained results were analyzed statistically, and significance of results was evaluated (GraphPad InStat 3.10). Interventions were found to be significantly effective in reducing Daha, Amlodgara, Shula, Chhardi, and Avipaka and associated symptoms with P < 0.001, more percentage relief was found in Daha, Amlodgara, and Shula in patients treated with the standard drug. After 1 month of treatment, more sustained response was observed in patients treated with Khanda Pippali Avaleha. In Group A, only 7.69% show relapse to moderate improvement after having marked improvement. In Group B, 16.66% show relapse from marked to mild improvement. Conclusion: A small attempt has been made to prove Khanda Pippali Avaleha is quite promising and efficacious treatment; its efficacy can be better interpreted by conducting a clinical trial on large sample.